Windblown sand along railway infrastructures: A review of challenges and mitigation measures. Issue 177 (June 2018) - Bruno, Luca; Horvat, Marko; Raffaele, Lorenzo
Abstract: The engineering interest about windblown sand is dictated by the harmful interactions between sand and a number of human infrastructures in arid environments. Particularly, the ongoing grand railway projects in the deserts of Far East, Middle East and North Africa regions require robust technical solutions to guarantee the efficient railway performance. The huge competences of the railway industry, traditionally developed in non-arid regions, should be developed and complemented to face mentioned challenges. The rationale problem setting, design, quantitative analysis and verification of sand mitigation measures are at present not sufficiently developed. The paper introduces original categorizations of both the windblown sand-induced performance deficiencies of the railway systems (windblown Sand Ultimate and Serviceability Limit States) and the prevention techniques to mitigate the windblown sand effects (Source-Path-Receiver categorization of the Sand Mitigation Measures). The state of the art is reviewed in the attempt to present the classification as accurately as possible. The main goal of the classification is to provide an orienting framework for scholars, railway owners, designers, general contractors and operators. We suggest the presented framework as a structured and organic base to properly set up future research activities, project terms of reference, most suited design solution, plan maintenance practices. Highlights: We reviewed the state of art of windblown sand effects and solutions along railways. Windblown sand effects are classified in Ultimate and Serviceability Limit States. Windblown Sand Mitigation Measures are classified by a Source-Path-Receiver scheme. Aerodynamics and sand morphodynamics around Mitigation Measures are discussed.